Scoping the emerging role of urban biodiversity in social impact assessment, a systematic review of regulating ecosystem services indicator types - Ayatollahi, Asef; Morello, Eugenio (Frontiers in Sustainable Cities, 2025)
The relationship between humans and nature in urban areas is complex, with dynamic interdependencies that require in-depth evaluation to aid planners in decision-making. While knowledge of social values and impacts of nature-based solutions (NbS) is progressing, a notable gap exists in integrating urban biodiversity (UB) and ecosystem services (ES) into evaluations. The increasing recognition of UB values raises questions about how biodiversity emerges as a new primary parameter in assessment. What are the leading indicators of ES in assessing the social impacts of NbS in cities? How can we integrate ES and UB into social impact assessment (SIA) as the primary framework for identifying, monitoring, and evaluating the social consequences of NbS in urban areas? This contribution undertakes a non-systematic exploratory investigation combined with a systematic literature review on regulating ES indicators to address these questions. Focusing on regulating ES, we screened 696 and analyzed 65 publications to identify and extract 85 indicators for SIA procedures. By elaborating on attributes, measurement methods, and approaches of indicators, we introduce six categories of classifications, revealing biodiversity-related indicators as an emerging trend in literature with considerable flexibility for measurement in urban areas. We conclude with emphasis on existing limits of scientific references on regulating ES indicators for social impact, as well as minor attention paid by scholars to the role of UB. Further research requires the comprehensive integration of UB and ES in SIA.